The Desire to Achieve "Normalcy" - Peter Schneider's Post-Wall Berlin Novel Eduard's Homecoming - Siegfried Mews (Studies in 20th & 21st Century Literature, 2004)
As one critic correctly observed on the occasion of Peter Schneider's sixtieth birthday (21 April 2000), the author's life and work have been defined by two momentous events whose import far surpasses that of happenings of merely local significance (see Karasek)...
Keywords: Peter Schneider; normalcy; Karasek; Eduard' s Homecoming; Berlin; reunification; post-wall; post-wall Berlin; 2000; 60; sixty; sixtieth birthday; Eduards Heimkehr